Imaging Ballistic Injuries. Issue 3 (August 2020) - Ditkofsky, Noah G.; Maresky, Hillel; Mathur, Shobhit
Here in Canada, we often think of gun violence as confined to conflict zones, terrorism, and more of a problem for our southern neighbor. However, in recent years, it has also become a Canadian problem with increased gun violence related to criminal activity presenting in daily practice. Radiologists play a critical role in the evaluation of ballistic trauma and must therefore be familiar with both the common and uncommon patterns of ballistic injury. In this article, we review the mechanisms of ballistic trauma as well as their resultant injury patterns in order to guide image interpretation.